SIGNIFICANT QUALITIES OF A SPORTS SCHOOL COACH RURAL MUNICIPALITY - Manzheley, I.V.; Gladkova, N.S.; Ivanova, S.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to study the professionally significant qualities of a children’s coach in the opinion of three subjects of a rural municipality: coaches, athletes and parents. Methods and structure of the study. Scientific work was carried out in 2022 at the Municipal Autonomous Institution of Additional Education for Children and Youth Sports School No. 2 of the Tyumen district of the Tyumen region with the involvement of coaches (16 people), teenage athletes (256 people) and their parents (278 pers.). The sample consisted of 550 people aged 10 to 69 years. During the study, an online survey was organized using structured questionnaires of three types "Coach", "Athlete", "Parent", consisting of 10 blocks of questions. In one of the blocks, the respondents were asked questions about the significant qualities of an ideal and real children’s coach and a list of them was proposed, with a proposal to evaluate them on a 10-point scale. Results and conclusions. It was revealed that the ideas about the image of the ideal children’s coach, which have developed in the minds of the coaches themselves and the parents of athletes, exceed the assessment of a real coach in most qualities and differ from the assessment of teenage athletes, in whose minds a real coach is better than an ideal one.